(untitled)
The study presents the content of moisture, fat, protein, ash and carbohydrate in some selected fish of Bangladesh. The study fishes include Ketchki fish Coria soborna, Hamilton-Buchanan, 1822), Molafish (Amblypharyngodonmola, Hamilton-Buchanan, 1822), Poah fish Panna microdon, Bleeker,1842), Tilapiafish (Oreochromismossambic, Peter, 1852), Silver carp fish (Hypohthalmichthys molitrix, Hamilton-Buchanan, 1822), Ruhi fish(Labeo rohita, Hamilton- Buchanan, 1822), Takhi fish Channa punctatus, Bloch&Schneider, 1801), Pangasfish (Pangasius pangasius, Hamilton-Buchanan, 1822). The moisture content, in present study, was found to be in range of 71.9-80.73g%. Protein content was found in the range of 12.96-17.18g%. Ash content in the fish was found to be in range of 1.47-11.76g%. Fat content was found in the range of 1.4-11.76g%. Carbohydrate content in the fish was found to be in range of 1.04-3.5g%. Total calorie content in the fish was found to be in a range of 83.39-169.30Kcal/100g. Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 19-23 , number=1, journal=Bangladesh Journal of Nutrition, year=2018, month=Dec., pages=19–23